A study of severity of intention of suicide in various psychiatric diagnoses - Pradhan, SN; Adhikary, SR (Kathmandu University Medical Journal, 2009)
Background: Suicidal intent has been described as the seriousness or intensity of the patient’s wish to terminate his or her life. Suicide has become an important public health issue throughout the world. It is important to evaluate the intentions of suicide attempts and various psychiatric diagnostic perspectives to understand the multiple dimensions of suicide. Aims: The aim of the work was to study the severity of suicidal intention among suicide attempters in different psychiatric diagnoses and different mode of attempted suicide. Materials and methods: This study was carried out in the patients, who attempted suicide, by various modes, who were admitted in the wards of KMCTH during 1st January 2007 to 30th December 2007. Suicide Intent Scale (SIS) was used in all the cases that had attempted suicide. Results: Total numbers of patients was 43. Mean SIS was 13.88. The results have shown that majority of cases were female 69.8% (n=30) and male were 30.2% (n=13).The commonest mode of suicide was poisoning 83.7% (n=36) in which moderate suicide intent was 58.3% (n=21); mild suicide intent 33.3% (n=12) and severe suicide intent 8.3% (n=3). Pesticide (organophosphorus) ingestion was the commonest mode of suicide 44.4% (n=16), followed by pharmacological drugs 33.3% (n=12). The commonest psychiatric diagnosis was depressive disorders 62.9% (n=27), in which moderate suicide intent was found to be maximum 70.4% (n=19) followed by mild suicide intent 14.8% (n=4) and severe suicide intent 14.8% (n=4). Conclusion: The increasing problem of pesticide poisoning and drug overdose demands strict legal scrutiny in the availability of common means of attempting suicide. Key words: Attempted suicide, Suicide intent scale, Organophosphorous poisoning, psychiatric diagnoses doi: 10.3126/kumj.v7i1.1768 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 63-66